(untitled) (Cardiovascular Journal, 2020)
Covid-19 pandemic has affected millions of patients, killed more than half a million, and poses major health threat globally. There is high demand for clinical resources and bed space for COVID- 19 patients. Admission of patient of any cardiac emergency in a common block of hospital, country like Bangladesh, may exposes the risk of infection among non-COVID patient. Patient with COVID- 19 and pre-existing cardiovascular diseases (CVD) have increased risk of further aggravation and death. COVID-19 infection is usually associated with multiple direct and indirect cardiovascular complications, such as acute myocardial injury, myocarditis, arrhythmias, heart failure and venous thromboembolism. Health care worker may pose themselves in vulnerability as they become host or vectors of virus transmission. Defeating COVID-19 and managing acute cardiovascular emergencies in COVID-19 era exposes non-COVID-19 patient, may need dramatic reshaping of care delivery, novel approaches to patient’s management and large-scale reallocation of resources. Cardiovasc. j. 2020; 13(1): 75-80